Effects of high-intensity interval training on canoeing performance - Yang, M.-T.; Lee, M.-M.; Hsu, S.-C.; Chan, K.-H. (European Journal of Sport Science, 2017)
The purpose of this study was to compare the effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) utilizing a canoeing ergometer on endurance determinants, as well as aerobic and anaerobic performances among flat-water canoeists. Fourteen well-trained male flat-water canoeists were divided into an HIIT group or an MICT group. All subjects performed a continuous graded exercise test (GXT) and three fixed-distance (200, 500, and 1000 m) performance tests on a canoeing ergometer to determine canoeing economy, peak oxygen uptake (VO2peak), and power at VO2peak, and to calculate the critical velocity (CV) and anaerobic work capacity before and after the training programmes. The training programme involved training on a canoeing ergometer three times per week for four weeks. HIIT consisted of seven 2 min canoeing bouts at an intensity of 90% VO2peak separated by 1 min of rest. The MICT group was trained at an intensity of 65% VO2peak continuously for 20 min. After four weeks of training, performance in the 200-m distance test and the power at VO2peak significantly improved in the HIIT group; performance in the 500 m and 1000 m distances and CV significantly improved in the MICT group. However, all variables were not significantly different between groups. It is concluded that HIIT for four weeks is an effective training strategy for improvement of short-distance canoeing performance. In contrast, MICT improves middle-distance canoeing performances and aerobic capacity.